Development of New Efficient Adsorbent by Functionalization of Mg3Al-LDH with Methyl Trialkyl Ammonium Chloride Ionic Liquid - Samuel Nick Țolea; Laura Cocheci; Lavinia Lupa; Raluca Vodă; Rodica Pode (Molecules, 2021)
The present paper describes a new way of obtaining an efficient adsorbent material by functionalization of Mg3Al layered double hydroxides (LDH) with methyl trialkyl ammonium chloride-ionic liquid (IL) using two methods: ultrasound and cosynthesis. Layered double hydroxides are good solid support for the functionalization with ionic liquids due to their well-ordered structure. The immobilization of the ILs in suitable solid supports combine the advantages of the ILs with the properties of the solid supports bringing more benefits such as use of lower quantity of ILs and avoiding of ILs loss in the aqua phase which overall decrease the treatment costs. In case of ultrasound method of functionalization is assured a uniform distribution of IL on the solid surface, but through immobilization by cosynthesis due to the tunable properties of LDH, is assured an intercalation of the ILs between the LDH layers. This fact was highlighted by the X-ray diffraction (RXD), scanning electron microscopy (SEM) analyses and Fourier-transform infrared (FTIR) spectroscopy of the obtained adsorbent. The added value brought by the functionalization of Mg3Al with the studied IL was underlined by the adsorption studies conducted in the treatment process of water with diclofenac content. Kinetic, thermodynamic, and equilibrium studies were performed. DCF adsorption onto the studied materials correspond to a chemisorption, the pseudo-second-order kinetic model describing the most accurately the experimental data. DCF adsorption onto the studied materials occurs as a heterogeneous process, with the experimental data fitting best with the SIPS isotherm. The sample obtained through cosynthesis developed a maximum adsorption capacity of 648 mg/g.